Remplacement total des artémia par des microparticules inertes dans l'élevage larvaire de l'ombrine Sciaenops ocellatus en Martinique - Petton, Bruno; Falguiere, Jean-claude (Proceedings of the 59th Annual Gulf and Caribbean Fisheries Institute, 2006)
In most of marine fishes cultured, larvae in their early development are fed with live prey (rotifer and/or artemia). In hatcheries, culture of these preys is labour consuming, needs specific facilities and represent an important part of production cast. On the other hand, world artemia production is subjected to fluctuation of harvest in the wild which could Iimit fish farming industry in the near future. A dried formula adapted to marine fish larvae has been perfected by Ifremer's center of Brest (France) and is distributed by a feeding company since 1999. This artificial microbound diet has been successfully tested on several temperate fishes such as European seabass (Dicentrarchus labrax), Atlantic cod (Gadus morhua) or European seabream (Sparus aurata) in a co-feeding (i.e. artemia and dried diet) strategy. Experiments described here were carried out ta evaluate the performances obtained during total substitution of artemia by this diet in Red drum (Sciaenops ocellatus) larval culture. ln 2004 and 2005, four experiments were conducted on feed technology aspects (experimental or industrial manufacturing), weaning strategy (direct or co-feeding) and feed distribution method (prototypes or classical self feeder) in comparison to the standardized method using live preys. At the end of larval phase (day 15) and at day 30, end of nursery phase (0.6 g), survival relative to control (RTC) was respectively 96.9% and 111.0% in the best treatment. Concerning growth, the weight RTC reached at day 15 and day 30 was respectively 82.8% and 72.4%. However, it is important to note that rearing protocols have to be adapted ta the use of these micro pellets in order toprevent degradation of culture quality. These results show that this new product can be applied on industrial scale in private hatcheries. But further research is needed ta evaluate replacement of rotifers by this dried formula in order to completely eliminate live prey in larval culture of Red drum. Dans la plupart des poisons marins élevés, les larves sont ...